2015
DOI: 10.2214/ajr.14.13459
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Susceptibility Mapping of the Motor Cortex in Amyotrophic Lateral Sclerosis and Primary Lateral Sclerosis

Abstract: Objective Diagnosis of amyotrophic lateral sclerosis (ALS) and primary lateral sclerosis (PLS) is often difficult due to absence of disease biomarkers. Our aim was to investigate quantitative susceptibility mapping (QSM) of the motor cortex as a potential quantitative biomarker for the diagnosis of ALS and PLS. Materials and Methods Utilizing an institutional review board approved retrospective database, QSM images for 16 patients with upper motor neuron disease (12 with ALS and 4 with PLS; mean age 56.3; 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 32 publications
9
84
0
1
Order By: Relevance
“…The pronounced T2* signal hypointensity in M1 of ALS patients has been reported by recent MRI studies (Ignjatović et al, 2013, Kwan et al, 2012, Schweitzer et al, 2015). However, we observed that M1 appears hypointense also in healthy controls and is not, by itself, an accurate biomarker of ALS.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The pronounced T2* signal hypointensity in M1 of ALS patients has been reported by recent MRI studies (Ignjatović et al, 2013, Kwan et al, 2012, Schweitzer et al, 2015). However, we observed that M1 appears hypointense also in healthy controls and is not, by itself, an accurate biomarker of ALS.…”
Section: Discussionsupporting
confidence: 68%
“…One recent study conducted on a 3 T MRI system observed an increase in χ in the M1 of ALS patients (Schweitzer et al, 2015) however the specificity of such increase to the cortical deep layers and its relation with patients' clinical conditions was not reported. In fact, rather than being a candidate direct biomarker of ALS, our results show that χ in M1 correlates with UMN impairment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Biophysically, susceptibility MRI (R2* and quantitative susceptibility mapping [QSM]) can detect local magnetic susceptibility changes that are sensitive to metals like iron . The apparent transverse relaxation rate (R2*) and QSM have been utilized to detect the distinct pathological patterns in PD, MSA, and PSP .…”
mentioning
confidence: 99%